Väinö Tanner and the discourse on racial difference - Nyyssönen, Jukka (Arctic and North, 2017)
The article charts a previously lesser-known aspect of research on the Skolt Sami by Väinö Tanner — his ideas on the Skolt Sami as a race. Tanner’s place in the scholarly field of racial theorizing and the discursive resources on which he relied are examined. One inspiring contemporaneous discourse was the Finnish hygienic discourse and the improvement of the nation’s health, towards which Tanner leaned. He reproduced aspects of the more aggressive eugenic discourse articulated by his ethnic peers, the Finland-Swedes, but the discourse on their racial superiority was unusable, given the agenda of his book, to elevate the Skolt Sami in the racial hierarchies. The economic organization of society was decisive for Tanner, rather than race, making him a Social evolutionist.